Human RIF1 and protein phosphatase 1 stimulate DNA replication origin licensing but suppress origin activation. (11th January 2017) - Hiraga, Shin‐ichiro; Ly, Tony; Garzón, Javier; Hořejší, Zuzana; Ohkubo, Yoshi‐nobu; Endo, Akinori; Obuse, Chikashi; Boulton, Simon J; Lamond, Angus I; Donaldson, Anne D
Abstract: The human RIF1 protein controls DNA replication, but the molecular mechanism is largely unknown. Here, we demonstrate that human RIF1 negatively regulates DNA replication by forming a complex with protein phosphatase 1 (PP1) that limits phosphorylation‐mediated activation of the MCM replicative helicase. We identify specific residues on four MCM helicase subunits that show hyperphosphorylation upon RIF1 depletion, with the regulatory N‐terminal domain of MCM4 being particularly strongly affected. In addition to this role in limiting origin activation, we discover an unexpected new role for human RIF1‐PP1 in mediating efficient origin licensing. Specifically, during the G1 phase of the cell cycle, RIF1‐PP1 protects the origin‐binding ORC1 protein from untimely phosphorylation and consequent degradation by the proteasome. Depletion of RIF1 or inhibition of PP1 destabilizes ORC1, thereby reducing origin licensing. Consistent with reduced origin licensing, RIF1‐depleted cells exhibit increased spacing between active origins. Human RIF1 therefore acts as a PP1‐targeting subunit that regulates DNA replication positively by stimulating the origin licensing step, and then negatively by counteracting replication origin activation. Synopsis: Human RIF1 protein forms a complex with PP1 that limits phosphorylation of MCM proteins to control S‐phase progression. RIF1‐PP1 also protects ORC1 from phosphorylation‐dependent degradation, to ensure full origin licensing in G1 phase. Human RIF1 interacts with protein phosphatase 1 (PP1) via its PP1 interaction motifs. RIF1‐PP1 controls the phosphorylation status of MCM proteins to negatively regulate DNA replication. RIF1‐PP1 stabilizes ORC1 protein, by counteracting CDK‐mediated phosphorylation that triggers ORC1 proteasomal destruction. RIF1‐PP1 therefore ensures full origin licensing by protecting ORC1 in G1 phase. Abstract : Human RIF1 protein forms a complex with PP1 that limits phosphorylation of MCM proteins to control S‐phase progression. RIF1‐PP1 also protects ORC1 from phosphorylation‐dependent degradation, to ensure full origin licensing in G1 phase.